Zinc Oxide Nanoparticle Improves the Intestinal Function of Intrauterine Growth Retardation Finishing Pigs via Regulating Intestinal Morphology, Inflammation, Antioxidant Status and Autophagy - Zhou, Binbin; Zhang, Jiaqi; Liu, Huijuan; Chen, Shun; Wang, Tian; Wang, Chao (Frontiers in Veterinary Science, 2022)
This study was to investigate effects of zinc oxide nanoparticle (Nano-ZnO) on growth, immunity, intestinal morphology and function of intrauterine growth retardation (IUGR) finishing pigs. Six normal birth weight (NBW) and 12 IUGR male piglets were obtained and weaned at 21 d. NBW-weaned piglets fed basal diets (NBW group), IUGR-weaned piglets allocated to two groups fed basal diets (IUGR group) and basal diets further supplemented 600 mg Zn/kg from Nano-ZnO (IUGR+Zn group), respectively. All pigs were slaughtered at 163 d. Results showed: (1) IUGR pigs showed no difference in body weight at 77d and 163d (P > 0.05), while had increased villus height (VH) and villus surface area in jejunum (P < 0.05) and enhanced interleukin-6, TNF-α and NF-κB mRNA expression (P < 0.05) as compared to NBW group; Compared with IUGR group, dietary Nano-ZnO did not affect the body weight (P > 0.05), but increased VH to crypt depth ratio and IgA concentration (P < 0.05) and decreased TNF-α and NF-κB mRNA expression in jejunum (P < 0.05). (2) IUGR increased the number of swollen mitochondria and autolysosomes, and protein expressions of sequestosome-1 (P62) and microtubule-associated protein light chain 3 B/A (LC3B/A) in jejunum as compared to NBW group (P < 0.05); Compared with IUGR group, Nano-ZnO decreased the number of swollen mitochondria and autolysosomes, and P62 and LC3B/A protein expression (P < 0.05). (3) IUGR increased mucosal contents of malondialdehyde and protein carbonyl (PC) and Keap1 protein expression (P < 0.05) as compared to NBW group; Compared with IUGR group, dietary Nano-ZnO increased activities of total antioxidant capacity, catalase, glutathione peroxidase, and glutathione content (P < 0.05), and enhanced nuclear respiratory factor 2 (Nrf2), glutamate-cysteine ligase modifier subunit and glutathione peroxidase 1 mRNA expression, and increased total and nuclear Nrf2 protein expression (P < 0.05), and decreased malondialdehyde and PC content, and Keap1 protein expression (P < 0.05) in jejunum. Results suggested that IUGR pigs showed postnatal catch-up growth and improved intestinal morphology, and dietary Nano-ZnO may further improve intestinal morphology, reduce inflammation, decrease autophagy and alleviate oxidative stress via Nrf2/Keap1 pathway in jejunum of IUGR pigs.